Complete percutaneous repair of Tetralogy of Fallot in adult: a case report - Asit Das; Gaurav Lakhani; Debdatta Kar; Lopamudra Mishra; Nur Nabab Mollah; Shubham Tewary (Journal of Cardiothoracic Surgery)
Abstract Tetralogy of Fallot (TOF) is the most common congenital cyanotic heart disease and is characterized by an antero-superior deviation of the infundibular septum with a consequent large malaligned ventricular septal defect (VSD) and a pulmonary and sub-pulmonary (infundibular) stenosis. Surgical repair has been the cornerstone of treatment that is electively performed early in their lives between 3 and 6 months of age. With advancements in transcatheter interventions, the complete percutaneous repair of TOF, a complex disease with multiple treatable lesions, is becoming a conceivable possibility. Here, we report the case of total transcatheter correction of an 18-year-old boy with TOF, performed in two stages. The first stage involved addressing the right ventricular outflow tract (RVOT) obstruction with balloon pulmonary valvuloplasty (BPV) and occluding the conal artery using absolute alcohol and a coil. In the second stage, the VSD was closed with a Multifunctional Occluder (MFO) Konar device 14 –12 mm (Lifetech, China). While surgical treatment remains the gold standard for total correction of TOF, the transcatheter approach can also be considered for selected group of patients who are surgically turned-down.